Policy responses to rapidly transforming midstream value chain segments in Africa: The case of the millet sector in Senegal - Tadesse, Getaw; Badiane, Ousmane (International Food Policy Research Institute, 2020)
This chapter aims to assess the performance of and policy responses to Africa’s rapidly emerging traditional staples value chains, which are dominated by small and medium-sized enterprises (SMEs) in the processing and trading segments. It addresses questions related to policy process issues such as (1) whether public intervention policies in Africa are in line with the needs and performance of the rapidly transforming value chains, and (2) how African governments should align policy interventions in emerging mid-chain segments to foster effective value chain development. The chapter uses the example of one of the most dynamic and fastest-growing staples value chains in Africa, the millet value chain in Senegal, thus contributing specifically to Senegal’s agro-industrial policy discourse. We begin with a review of value chain development evolution as a concept and in practice in Africa as a whole and outline a comprehensive list of critical policy concerns and priorities that must be addressed to respond to the needs of midstream value chain segments.